2016
DOI: 10.3390/ani6020013
|View full text |Cite
|
Sign up to set email alerts
|

Look Before You Leap: What Are the Obstacles to Risk Calculation in the Equestrian Sport of Eventing?

Abstract: Simple SummaryThis paper examines a number of methods for calculating injury risk for riders in the equestrian sport of eventing, and suggests that the primary locus of risk is the action of the horse jumping, and the jump itself. The paper argues that risk calculation should therefore focus first on this locus.AbstractAll horse-riding is risky. In competitive horse sports, eventing is considered the riskiest, and is often characterised as very dangerous. But based on what data? There has been considerable res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…More specifically, a major concern has been athlete and horse falls at jumps during cross-country which can potentially have very serious consequences for both horse and athlete. 2,3 Safety in eventing was subject to a major review following five high-profile athlete fatalities in the UK in 1999 alone, 4 and the following year the International Eventing Safety Committee (IESC) reported their findings, concluding that the primary focus of improving safety for both horses and athletes should be to 'prevent horses from falling'. 5 In the two decades since the IESC report, there have been many rules revisions and developments in the sport.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, a major concern has been athlete and horse falls at jumps during cross-country which can potentially have very serious consequences for both horse and athlete. 2,3 Safety in eventing was subject to a major review following five high-profile athlete fatalities in the UK in 1999 alone, 4 and the following year the International Eventing Safety Committee (IESC) reported their findings, concluding that the primary focus of improving safety for both horses and athletes should be to 'prevent horses from falling'. 5 In the two decades since the IESC report, there have been many rules revisions and developments in the sport.…”
Section: Introductionmentioning
confidence: 99%
“…5 In the two decades since the IESC report, there have been many rules revisions and developments in the sport. 2 There have also been at least 50 athlete fatalities and at least 109 horse fatalities worldwide at all levels of competition. 3 In the intervening years to today, there have only been a handful of academic studies published that attempted to quantify the risk factors associated with falls during cross-country: all those were published before 2009 and were based on data from the 2001/2002 season.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of previous research about the inherent dangers of horses and some behaviours that can cause serious injury or human fatality, humans will continue to domesticate equids (horses, mules and donkeys) for work or non-work purposes. Therefore, the inherent risk of human-horse interaction remains unchanged [18].…”
Section: Introductionmentioning
confidence: 99%
“…The primary limitation of this study is related to reporting compliance, as previously described by O’Brien. 16 It is suggested that there is an overestimate of serious injuries in incident report data due to non-reporting when a fall leaves a rider uninjured. 16 USPC has attempted to address this with presentations to local and regional leadership indicating the importance of filling out incident reports any time a rider falls off, and not just when there is an injury.…”
Section: Discussionmentioning
confidence: 99%